DO CUTICLE CHARACTERS SUPPORT THE RECOGNITION OF ALSEO- DAPHNE, NOTHAPHOEBE & DEHAASIA AS DISTINCT GENERA? - Sachiko Nishida; Henk van der Werff (BRIN Publishing (Penerbit BRIN), 2014)
NISHIDA, S. & VAN DER WERFF, H. Do cuticle characters support the recognition of Alseodaphne, Nothaphoebe and Dehaasia as distinct genera? Reinwardtia 14(1): 53 – 66. ? The Asian members of the Persea group are divided among the genera Alseodaphne, Apollonias, Dehaasia, Machilus, Nothaphoebe and Phoebe. A recent phylogenetic analysis has shown that Machilus and Phoebe are supported as monophyletic genera but evidence that the closely related genera Alseodaphne, Dehaasia and Nothaphoebe are monophyletic or not was equivocal. In this study we analyzed cuticle characters of 95 collections belonging to the Asian members except for Apollonias. We anticipated two possible outcomes. If the genera were not monophyletic, we expected that the groups based on cuticle characters would consist of species belonging to different genera. If the genera were monophyletic, we expected that the groups based on cuticle characters would consist of species belonging to the same genus. We found 16 groups based on cuticles. Of these, 12 consisted of species of a single genus (one group included a single species and thus a single genus). The four mixed groups included mostly species of one genus with 1 or 2 species of a different genus. Our results support the recognition of Alseodaphne, Dehaasia, Machilus, Nothaphoebe and Phoebe as distinct genera.